Primary Malignant Melanoma of the Hard Palate: A Rare Case Report - Putri, Syifa Azizah; Kiki Ahmad Rizki (HM Publisher, 2024)
Background: Primary malignant melanoma of the oral cavity is an uncommon and aggressive malignancy with a poor prognosis. The hard palate is a rare site for primary melanoma, and early diagnosis is often challenging due to its asymptomatic nature in the initial stages. Case presentation: We present the case of a 58-year-old female who presented with a pigmented lesion on the right hard palate and a neck mass. The lesion had been present for a year and had gradually increased in size. The neck mass had appeared three months prior and was associated with pain. Imaging and biopsy confirmed the diagnosis of malignant melanoma with cervical lymph node metastasis. The patient underwent wide excision with right hemimaxillectomy and modified radical neck dissection type II, followed by planned postoperative radiation therapy. Conclusion: This case highlights the importance of considering melanoma in the differential diagnosis of pigmented oral lesions. Early diagnosis and aggressive treatment are crucial for improving outcomes in this rare but aggressive malignancy. The use of adjuvant therapies, such as radiation and targeted therapy, may be beneficial in select cases.